2013
DOI: 10.1111/joim.12144
|View full text |Cite
|
Sign up to set email alerts
|

Ceruloplasmin and atrial fibrillation: evidence of causality from a population‐based Mendelian randomization study

Abstract: Objectives. Inflammatory diseases and inflammatory markers secreted by the liver, including C-reactive protein (CRP) and ceruloplasmin, have been associated with incident atrial fibrillation (AF). Genetic studies have not supported a causal relationship between CRP and AF, but the relationship between ceruloplasmin and AF has not been studied. The purpose of this Mendelian randomization study was to explore whether genetic polymorphisms in the gene encoding ceruloplasmin are associated with elevated ceruloplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…(7) Our study confirms and extends these findings to the large, middle-aged, biracial cohort of men and women in the ARIC study. After adjusting for traditional risk factors and different biomarkers, higher levels of circulating CP were associated with incident AF.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…(7) Our study confirms and extends these findings to the large, middle-aged, biracial cohort of men and women in the ARIC study. After adjusting for traditional risk factors and different biomarkers, higher levels of circulating CP were associated with incident AF.…”
Section: Discussionsupporting
confidence: 87%
“…In this same study, a variant of rs11708215, a single nucleotide polymorphism (SNP) located in the CP gene promoter, was associated with both higher CP concentrations in blood and increased AF risk. (7) These results, however, have not been replicated in other studies. Another SNP, rs13072552, also in the CP gene, has been associated with CP plasma concentration.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Maternal obesity has also been linked to inflammation 23. Since inflammation is a well‐known AF risk factor, one can speculate that some of the risk of AF associated with high maternal BMI could perhaps be mediated through upregulation of inflammatory pathways in the offspring 24. Prevalence of obesity among fertile women is rising, with implications for the health of future generations 25.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have demonstrated that Cp may act as an oxidase to nitric oxide [4], and may adversely impact on endothelial function [5]. An emerging literature also supports an important role of Cp in the development of neurodegenerative diseases [6] and in atrial fibrillation [7], suggesting a potential pathogenic role of Cp.…”
Section: Introductionmentioning
confidence: 99%